Colloid Process Engineering - Kind, Matthias.; Kind, Matthias.; Peukert, Wolfgang.; Peukert, Wolfgang.; Rehage, Heinz.; Rehage, Heinz.; Schuchmann, Heike P.; Schuchmann, Heike P. (Springer International Publishing : Imprint: Springer, 2015)
This book deals with colloidal systems in technical processes and the influence of colloidal systems by technical processes. It explores how new measurement capabilities can offer the potential for a dynamic development of scientific and engineering, and examines the origin of colloidal systems and its use for new products. The future challenges to colloidal process engineering are the development of appropriate equipment and processes for the production and obtainment of multi-phase structures and energetic interactions in market-relevant quantities. The book explores the relevant processes and for controlled production and how they can be used across all scales.